The impact of health literacy, sense of purpose, and self-compassion on the quality of life of students at the Islamic Azad University branches in Tehran - Arshadi , Yalda; Kamyabi, Mitra; Hajipour Abaie , Najmeh; Andishmand , Vida (Social Determinants of Health, 2025)
Background: The current investigation set out to investigate the effects of compassion for oneself, sense of mission, and health knowledge on the standard of life of students at the Tehran campuses of Islamic Azad University. Method: The present research used a correlational and descriptive approach. All master's and doctorate students in humanities fields (literature, history, philosophy, and sociology) enrolled in the Islamic Azad University branches in Tehran during the 2024–2025 academic year, totaling over 50,000 students, made up the estimated population. The World Health Organization Quality of Life questionnaire, the Ryff goal in life scale, the Neff self-compassion scale, and the Montazeri et al. health awareness questionnaire were among the instruments used for gathering the data. Following the completion of the surveys, structural equation modeling tests and SPSS-24 and Smart-PLS software were used to evaluate the data. Results: The findings showed that students' quality of life is substantially enhanced by health knowledge, compassion for oneself, and a sense of purpose. In particular, students' quality of life was higher when they had greater levels of compassion for oneself, goals, and health awareness. Conclusion: Enhancing these variables among students can contribute to improving their quality of life, and these variables have a major impact in enhancing the quality of life of students.